(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research cancellations in life insurance policies and their impact on the solvency of the insurance companies (Applied Research in the Iraqi general insurance company), The study was descriptive approach in identifying and addressing variables which consists of cancellations in life insurance independent variable, the financial solvency of insurance companies as the dependent variable, and for the purpose of achieving the objectives of the research were formulated one hypothesis has been tested in the Iraqi insurance company, the researcher used the financial statements in the collection data needed for the study and information . The research found a number of conclusions highlighted that inflation, as well as economic variables among the insured and higher prices and the decline in the purchasing power of money, as well as thinking about buying needs more important than life insurance policies to the lack of the individual’s desire to continue life insurance to the small amounts of compensation compared with the level General prices, which lead to increased cancellation rates in life insurance policies, as well as social awareness among the insured and cultural level, adequate insurance and the extent to life with religious beliefs customers potential, the demand for life insurance is influenced by another factor, but it is over the rush of the individual toward the tunnels consumer, and savings in non-governor of self-insurance or savings in banks . He concluded Find a set of recommendations and proposals which concern promotional methods personal selling, advertising, sales promotion because it occupies an important position in the marketing of insurance service operations are working to draw the attention of the insured, and defined the benefits of insurance and the types of insurance coverage provided by insurance companies, and this leads to disseminate awareness of insurance as well, as well as the introduction of new products fit the needs of the insured, this is done by creating a data and information to familiarize themselves with all the information relating to the insured their base, depth study of behavioral characteristics for them to learn about their desires and expectations, as well as increasing the number of branches in the provinces and in line with a population density of each province.